2012
DOI: 10.1364/oe.20.028912
|View full text |Cite
|
Sign up to set email alerts
|

Computer modeling and experimental study of non-chain pulsed electric-discharge DF laser

Abstract: Computer simulation and experimental study of a pulsed electrical-discharge DF laser pumped by the SF(6)-D(2) non-chain reaction are presented. The computer model encompassing 28 reactions is based on laser rate equations theory, and applied to approximately describe the chemical processes of non-chain DF laser. A comprehensive study of the dependence of number density on time for all particles in the gain area is conducted by numerical calculation adopting Runge-Kutta method. The output performance of non-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It was found that, if there is a small-scale inhomogeneity ~50 µm at the cathode surface, an SSVD can develop in SF 6 and SF 6 -based mixtures in the form of a self-initiated volume discharge (SIVD) with its uniform character preserved even in the case of the discharge gaps possessing a high edge electric field enhancement [39]. All SIVD characteristics in SF 6 (form, current and voltage oscillograms) are identical to those of the SSVD triggered by UV [39,40] and x-ray preionization [41].…”
Section: Experiments and Ssvd Phenomenologymentioning
confidence: 97%
“…It was found that, if there is a small-scale inhomogeneity ~50 µm at the cathode surface, an SSVD can develop in SF 6 and SF 6 -based mixtures in the form of a self-initiated volume discharge (SIVD) with its uniform character preserved even in the case of the discharge gaps possessing a high edge electric field enhancement [39]. All SIVD characteristics in SF 6 (form, current and voltage oscillograms) are identical to those of the SSVD triggered by UV [39,40] and x-ray preionization [41].…”
Section: Experiments and Ssvd Phenomenologymentioning
confidence: 97%
“…The chemical reaction process of a non-chain HF laser is very complicated. Here, we only consider the following major processes [26,27],…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Also in 2015, Martyshkin reported a repetition rate Fe 2+ :ZnSe laser with a maximum average power of 35 W at 77 K [6]. Both the flash-lamp-pumped Er:YAG laser and the non-chain pulsed HF/DF laser pump source have the disadvantages of large volume and low wall-plug efficiency [11,12]. However, solid state continuous-wave Fe 2+ :ZnSe lasers using an LD pumped Er:YAG laser as the excitation source have the advantages of compact size and high wall-plug efficiency, which would have prospects in the future.…”
Section: Introductionmentioning
confidence: 99%